2023
DOI: 10.3389/fonc.2023.1223786
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the pan-immune-inflammation value in breast cancer patients

Xiaoyan Qi,
Boyang Qiao,
Tingting Song
et al.

Abstract: BackgroundThe newly discovered pan-immune-inflammation value (PIV) has been illustrated to have good prognostic value for cancer patient prognosis. However, the prognostic usefulness of PIV in breast cancer patients is unknown. As a result, to aid the clinic in providing a distinctive and trustworthy biomarker to better assess breast cancer patient’s prognosis, we conducted this meta-analysis to investigate the relationship between PIV and the survival of breast cancer patients.MethodsWe conducted a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
(60 reference statements)
2
2
0
Order By: Relevance
“…Furthermore, a total of meta-analyses involving 2953 breast cancer patients investigated the prognostic significance of PIV (including OS, PFS, pCR [pathological complete response]), revealing cutoff values ranging from 205.1 to 438.7. 37 The optimal PIV cutoff value of 363.47, as determined in this study, falls within the range consistent with above findings. Based on the PWR reference value, Zhao et al discovered that patients with a PWR value of more than 25.38 had a poor prognosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, a total of meta-analyses involving 2953 breast cancer patients investigated the prognostic significance of PIV (including OS, PFS, pCR [pathological complete response]), revealing cutoff values ranging from 205.1 to 438.7. 37 The optimal PIV cutoff value of 363.47, as determined in this study, falls within the range consistent with above findings. Based on the PWR reference value, Zhao et al discovered that patients with a PWR value of more than 25.38 had a poor prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…Utilizing a restricted cubic spline (RCS) model, they determined an optimal critical value for PIV at 308.2. Furthermore, a total of meta‐analyses involving 2953 breast cancer patients investigated the prognostic significance of PIV (including OS, PFS, pCR [pathological complete response]), revealing cutoff values ranging from 205.1 to 438.7 37 . The optimal PIV cutoff value of 363.47, as determined in this study, falls within the range consistent with above findings.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, PIV's predictive efficiency was significantly superior to previously recognized inflammation-related markers [38]. A meta-analysis conducted by Qi et al, involving eight articles and 2953 patients with breast cancer, showed that elevated PIV in patients correlated with shorter OS and PFS [39]. In the context of bladder cancer specifically, Kayar et al discovered that an elevated PIV (>406.29) was associated with diminished OS and DFS [17].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other inflammatory indexes, PIV combines all routinely assessed blood cell populations that reflect systemic inflammation and immunity. [ 109 ] As such, it provides a more complete picture of the host’s condition and is of more reliable value for prognostic assessment. However, there are few related studies on it, and more research is needed to explore it further.…”
Section: Peripheral Blood Inflammatory Indexes In Breast Cancermentioning
confidence: 99%